Single chain spectroscopy of conformational dependence of conjugated polymer photophysics - Huser, Thomas (The National Academy of Sciences, 2000)
Single molecule confocal fluorescence microscopy was used to perform photoluminescence spectroscopy on single, isolated molecules of the conjugated polymer poly[2-methoxy,5-(2′-ethyl-hexyloxy)-p-phenylene-vinylene] (MEH-PPV). We show that the fluorescence from single chains of this electroluminescent polymer depends strongly on chain conformation. The time evolution of the spectra, emission intensity, and polarization all provide direct evidence that memory of the chain conformation in solution is retained after solvent evaporation. Chains cast from toluene solution are highly folded and show memory of the excitation polarization. Exciton funneling to highly aggregated low energy regions causes the chain to mimic the photophysical behavior of a single chromophore. Chains cast from chloroform, however, behave as multichromophore systems, and no sudden discrete spectral or intensity jumps are observed. These also exhibit different spectroscopy from the folded chromophores.